Improving the Ability of Second Grade Students in Writing Words by Using Picture Media at SDN 3 Jogosetra - Nurmiana, Dewi Agus (Universitas Sebelas Maret, 2022)
This study aims to improve the ability of grade II students of SDN 3 Jogosetran, Kalikotes District, Klaten Regency in writing words using picture media. This study used a Classroom Action Research design conducted in two cycles through the same stages, namely planning, implementation, observation, and reflection. This research was conducted in class II of SDN 3 Jogosetran, Kalikotes District, Klaten Regency with a total of 9 students consisting of 3 male students and 6 female students. Data collection techniques used were observation and evaluation. The collected data were analyzed using qualitative and quantitative analysis techniques. The results showed that by using image media, learning activities became more enjoyable so that students' learning outcomes increased, namely the results from cycle I to cycle II there was an increase. In cycle I, the average score obtained by students was 64.33 with a classical completeness level of 45%, the incomplete score in cycle I was 55%, while in cycle II the average score obtained by students was 85.67 with a classical completeness level of 90% so that there was an increase in classical completeness by 50%. From these results, it can be concluded that the use of picture media can improve the ability to write words of grade II students.